AB1304 Semiquantitative assessment of inflammation in arthritis patients with indocyanine green enhanced optical imaging using for monitoring of treatment response. (23rd January 2014) - Werner, S.G.; Langer, H.-E.; Spiecker, F.; Mettler, S.; Lind-Albrecht, G.; Hermsen, C.; Backhaus, M.
Abstract : Background: Indocyanine green (ICG) enhanced fluorescence optical imaging (FOI) is a diagnostic tool for assessment of inflammation in arthritis. In cross-sectional studies FOI had a good agreement with MRI and US findings (1). The semiquantitative fluorescence optical imaging activity score (FOIAS) correlated with clinical (DAS 28) and MRI (RAMRI) scores of disease activity. Objectives: To compare clinical assessment and FOIAS for measurement of treatment response in DMARD naïve patients and in subjects with inadequate response to non-biologic DMARDs (DMARD-IR) and switch to biologicals. Methods: 57 cases with rheumatoid (RA) and psoriatic (PsA) arthritis were examined before starting treatment with non-biological or biological DMARD (visit 1) and at follow-ups (visits after ≥3 months). FOI (Xiralite, mivenion GmbH, 0.1 mg/kg/BW of ICG i.v. over 6 minutes) sequences were analyzed for FOIAS (PVM, P1, P2, P3) (1). Treatment response was assessed using DAS28, physicians global (VAS 1-10), swollen joint count (SJC), tender joint count (TJC), CDAI, SDAI and FOIAS. Standardized response means (SRM) were calculated for measurement of treatment response. Results: All scores showed a reduction of disease activity from visit 1 to visit 2. High treatment response (SRM >0.8) were seen for physicians global and DAS28, moderate response (SRM >0.5-0.8) for SJC, CDAI, SDAI, FOIAS PVM, P2 and P3 (2). Detailed results are shown in table . Conclusions: The study suggests that treatment monitoring with FOI and the semiquantitative FOIAS are a suitable tools to assess treatment response in subjects with RA and PsA treated with DMARDs or biologicals. Further studies are required to evaluate FOIAS as a possible additional outcome measure in clinical trials and clinical practice. References: Werner SG, Langer HE, Ohrndorf et al. Inflammation assessment in patients with arthritis using novel in vivo fluorescence optical imaging technology. Ann Rheum Dis Oct 12, Epub ahead of print. Husted JA, Cook RJ, Farewell VT, et al. Methods for assessing responsiveness: a critical review and recommendations. J Clin Epidemiol 2000;53:459–68. Disclosure of Interest: S. Werner Grant/Research support from: Pfizer, H.-E. Langer Grant/Research support from: Pfizer, F. Spiecker: None Declared, S. Mettler: None Declared, G. Lind-Albrecht: None Declared, C. Hermsen: None Declared, M. Backhaus Grant/Research support from: Pfizer